Inferior Vena Cava and Renal Vein Thrombosis Associated with Thymic Carcinoma. (10th January 2017) - Berbecar, Vlad Teodor; Jurubita, Roxana; Paraschiv, Marina; Obrisca, Bogdan; Sorohan, Bogdan; Ismail, Gener
Abstract : Thymic tumors are rare mediastinal tumors that can present with a wide variety of symptoms. They can cause distant manifestations and are frequently associated with paraneoplastic syndromes. In our case, we describe the evolution of a 68-year-old male whose first manifestation was thrombosis of the inferior vena cava and renal veins. Thrombosis of large abdominal veins is rare, especially without being associated with any other comorbidity or risk factors.